Investment strategies, fund performance and portfolio characteristics - Stefan Engström (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
This paper studies the relation between fund performance and the fund manager's investment strategy, which is based on the characteristics of the portfolio. The results show that neither momentum characteristics nor the valuation of stocks can explain differences in fund performance. However, the paper finds a negative firm-size effect that partly explains previous findings of a negative fund-size effect. Moreover, the results show a positive relation between performance and the degree of diversification within the fund portfolio. However, diversification by including non-listed stocks does not enhance performance.
Keywords: G11; G12; G23; 330; Diversification; Portfolio Evaluation; Investment Strategies; Momentum; Portfolio-Management; Investmentfonds; Schweden